Drivers of the tax effort : evidence from a large panel - Barros, Victor (2021)
This paper extends previous literature by assessing the drivers of tax effort in a large panel of 122 countries over the period 1980 to 2017 and refining the analysis to regions, periods, income group, and economic development level. Our focus is on five blocks of determinants, namely: economic, fiscal, openness, structural, and political. We find that tax effort is influenced by all blocks, although results differ per income group. Tax effort in advanced economies is driven by all blocks of drivers, except political variables, while openness, structural, and political blocks prevail in developing economies. There is no consistency regarding the determinants across the four regions (Latin America, Africa, Europe and Asia). We also find that during the first two decades under analysis, tax effort is mainly associated with both higher levels of countries’ tax revenues and the role of the agricultural sector in the economy, while from 1999 onwards the determinants are mainly driven by left-wing ruling governments and the economic and fiscal blocks of variables. Our results are robust for a battery of sensitivity and robustness tests. Taken all together, our findings suggest the existence of heterogeneous impacts, which implies that policies resulting in improvements in the level of tax effort can affect countries in different ways.